Integrated Service Quality Factors Influencing Revisit Intention among Café Amazon Customers in Mueang District, Narathiwat Province - Uma, Nurulakmawatee; Binchesoh, Sulfa; Arong, Nadia; Binseng, Munifah; U-senyang, Sarannee; Saaree, Roihan (Journal for Developing the Social and Community, 2026)
Background and Aims: The Thai coffee shop industry has become increasingly competitive, particularly in the southern border region, where distinctive cultural contexts and consumer behaviors remain insufficiently documented in empirical literature. This study integrates the SERVQUAL framework with three contextual variables - product quality, store atmosphere and environment, and brand image - to examine their influence on customers’ repurchase intentions at Café Amazon outlets in Mueang District, Narathiwat Province, a context that has not previously been investigated. Methodology: A quantitative research design was employed. Data were collected from 400 Café Amazon customers in the study area, with sample size determined using Cochran’s formula. A five-point Likert-type scale questionnaire was used to measure four independent variables and one dependent variable (repurchase intention). Multiple regression analysis was applied to test the hypothesized relationships. Results: All four independent variables exerted statistically significant positive effects on repurchase intention at the .05 level (p < .05), collectively explaining 59.5% of its variance (R² = .595, f² = 1.469). Brand image emerged as the strongest predictor (β = .238), indicating that customers in this locale place greater weight on brand credibility and perceived brand value than on tangible service attributes. This was followed by product quality (β = .204), service quality (β = .200), and store atmosphere and environment (β = .180), respectively. Conclusion: The findings extend empirical support for the SERVQUAL framework in a southern Thai border context and demonstrate that brand image exerts disproportionate influence over other service quality dimensions in this setting. Practically, operators should adopt a holistic service quality management approach with particular emphasis on consistently developing and sustaining brand identity to foster customer loyalty in this highly competitive local market.